Predicting respiratory distress syndrome at birth using fast test based on spectroscopy of gastric aspirates. 1. Biochemical part. (14th July 2019) - Schousboe, Peter; Verder, Henrik; Jessen, Torben E.; Heiring, Christian; Bender, Lars; Ebbesen, Finn; Dahl, Marianne; Eschen, Christian; Fenger‐Grøn, Jesper; Höskuldsson, Agnar; Reinholdt, Jes; Scoutaris, Nikolaos; et al.
Abstract: Aim: To develop a fast bedside lung maturity test. Methods: Gastric aspirates obtained from premature infants contain lamellar bodies, carrying lung surfactant. To estimate lung maturity, we isolated lamellar bodies from fresh gastric aspirates by centrifugation. Erythrocytes and other cells were lysed by adding water and discarded subsequently with the supernatant. Mid‐infrared spectroscopy was then performed to measure the lung maturity as lecithin–sphingomyelin ratio. Lecithin was determined as dipalmitoylphosphatidylcholine, the most surface‐active phospholipid. Algorithms to measure lecithin and sphingomyelin concentrations in fresh gastric aspirates were developed on aspirates from 140 premature infants. Each gastric aspirate sample was divided into two samples: one for mass spectrometry as reference and one for spectroscopy. Development of the algorithm is described in detail in Appendix S1. Results: Gastric aspirates stored at 4–5°C avoid flocculation of proteins and phospholipids in contrast to when the aspirates were frozen and thawed. Omission of freezing and concentration of the lung surfactant by centrifugation combined with diminished influence of proteins improves the spectroscopic measurement of lecithin–sphingomyelin ratio. Measurement of lecithin–sphingomyelin ratio by the new method was performed within 10–15 minutes. Conclusion: We present a new fast bedside lung maturity test on fresh gastric aspirate for early targeted surfactant treatment.